Relationship between the Use of Social Media and Knowledge on the Impact of Premarital Sexual Behavior during the Covid-19 Pandemic among Adolescents at SMA Negeri 10 Semarang - Diajeng Prasasti; Kartika Adyani; Friska Realita (EMBRIO: Jurnal Kebidanan, 2022)
Social media usage has increased by 40% during the Covid-19 pandemic since many people use social media to communicate during the pandemic. This increase in use has an impact on adolescents in the form of negative access to social media which has triggered various negative behaviors among adolescents. This study aims to determine the use of social media in seeking information regarding the impact of knowledge on premarital sexual behavior during the Covid-19 pandemic. It is expected that data regarding adolescents' knowledge on the use of social media can be a reference for content creators/writers on social media in a positive and more positive direction. Innovative to be easily accepted by teenagers. This was a quantitative analytic study with correlational design to determine the relationship between daily use of social media during the Covid-19 pandemic and knowledge on the impact of premarital sexual behavior among adolescents. The samples involved 88 students who were selected using purposive sampling technique. Data collection instrument was a questionnaire. Data were analyzed using Chi Square test. It was found that 50 respondents (56.8%) who used social media to find information on the impact of premarital sexual behavior had good knowledge and 7 respondents (7.95%) had poor knowledge. Meanwhile, 20 respondents (22.7%) who did not use social media to find information on the impact of premarital sexual behavior had poor knowledge and 11 respondents ​​(12.5%) had good knowledge. Analysis through Chi Square test obtained a p-value of 0.001 and correlation coefficient (r) 0.829 (>0.60). Therefore, it can be concluded that there was a significant relationship between the use of social media and knowledge on the impact of premarital sexual behavior among adolescents.